1988
DOI: 10.1111/j.1365-2923.1988.tb00793.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of medical education on the attitudes of medical students towards disabled people

Abstract: The negative attitudes of society towards disability and the resulting prejudicial behaviour affects the lives of disabled people. One of the declared aims of the Faculty of Medicine of the University of Southampton is to improve attitudes. Hence, an attempt has been made to assess differences in the attitudes held by first- and fourth-year medical students, senior house officers and members of the general public towards disabled people. The measurement instrument used was the 'Attitudes Towards Disabled Perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 19 publications
1
15
1
Order By: Relevance
“…Despite the shortage of research regarding nursing students' attitudes toward the disabled, there is substantial evidence in the literature of the relationship between education and the promotion of a positive attitude change toward disabled individuals (Berrol, 1984;Duckworth, 1988;Evans, 1976;Gething, 1986;Gruythuysen, 1987;Perry & Apostal, 1986). Other studies have found that contact with disabled individuals improved the attitudes of health professionals (Benham, 1988;Evans, 1976).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the shortage of research regarding nursing students' attitudes toward the disabled, there is substantial evidence in the literature of the relationship between education and the promotion of a positive attitude change toward disabled individuals (Berrol, 1984;Duckworth, 1988;Evans, 1976;Gething, 1986;Gruythuysen, 1987;Perry & Apostal, 1986). Other studies have found that contact with disabled individuals improved the attitudes of health professionals (Benham, 1988;Evans, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences in attitudes among these groups. Duckworth (1988) also found that medical students' attitudes toward people with physical disabilities did not change throughout their education.…”
Section: Literature Reviewmentioning
confidence: 93%
See 1 more Smart Citation
“…It is motivated also by the fact that the view is widespread in the literature of bioethics and health care economics. In fact, nondisabled health care professionals judge the QOL of disabled people to be even lower than the judgments made by nondisabled people who are not health care professionals (Duckworth 1988; Brillhart, Jay, and Wyers 1990; Bach and Tilton 1994; Gerhart et al. 1994; Albrecht and Devlieger 1999).…”
Section: Introductionmentioning
confidence: 94%
“…Individual physician attitudes can also impact policies at the institutional or societal level regarding allocation of resources toward PWDs. 2,3 The importance of cultural competency in dealing with disability will grow in the coming years as the number of patients with physical disability increases because of the aging of the population and young, disabled veterans returning from wars in Iraq and Afghanistan. Furthermore, communication with disabled or chronically ill patients is necessary across all medical specialties and is not limited to rehabilitation.…”
mentioning
confidence: 99%